Engineering and in vitro evaluation of acid labile cholesterol tethered MG132 nanoparticle fortargeting ubiquitin-proteasome system in cancer - Ghosh, Chandramouli; Gupta, Neha; More, Piyush; Sengupta, Poulomi; Mallick, Abhik; Santra, Manas Kumar; Basu, Sudipta (Chemistryselect, 2016)
In recent years, proteasome has evolved as one of the important alternative targets in cancer chemotherapy. However, selective targeting of proteasome system in cancer cells still remains a major challenge. To address this, a potent peptide based proteasome inhibitor MG132 was chemically conjugated with biocompatible-biodegradable cholesterol by acid cleavable hydrazone linkage. Spherical nanoparticles (MG132-NPs) were engineered from cholesterol-MG132 conjugate. Increased amount of free MG132 was released from these nanoparticles in acidic environment compared to physiological milieu in a slow and controlled manner. These MG132-NPs were taken up by breast cancer MCF7 cells into lysosomes within 6 h. Proteasome system was inhibited by these MG132-NPs leading to stabilization of beta-catenin, cyclin A and cyclin B in HEK-293T cells. Interestingly, MG132-NPs induced much improved cell death in drug resistant MDA-MB-231 cells with insignificant toxicity in healthy cells (HEK293 and L929) even in higher concentration.

Electrospinning of non-ionic cellulose ethers/polyvinyl alcohol nanofibers: characterization and applications - Wali, Ashwini; Zhang, Yucheng; Sengupta, Poulomi; Higaki, Yuji; Takahara, Atsushi; Badiger, Manohar V. (Carbohydrate Polymers, 2018)
The morphology of spin-coated films and electrospun fibers of ethyl hydroxy ethyl cellulose (EHEC), hydrophobically modified ethyl hydroxy ethyl cellulose (HM-EHEC) and their blends with Poly(vinyl alcohol) (PVA) was examined by AFM, SEM and contact angle measurements. These polysaccharides upon blending with PVA exhibited smooth surface which was evidenced by Atomic Force Microscopy (AFM) observation. The electrospinnability of above polysaccharides with PVA was demonstrated for the first time. The oriented fibers could be obtained using a rotating disc collector. Contact angles of spin-coated films and electrospun fibers were discussed in terms of hydrophobicity and wetting characteristics. Further, The nanofibers of EHEC/PVA were in-situ crosslinked using citric acid and were used for controlled release of an antibacterial drug, Chlorhexidine Digluconate (ChD). In-vitro studies of cytotoxicity, cell growth and cell proliferation were performed using L929 mouse fibroblast cells. These nanofiber mats show potential in drug delivery and as scaffolds in tissue engineering applications.
Keywords: cellulose; drug delivery; electrospinning; Ethyl hydroxy ethyl cellulose; Hydrophobically modified ethyl hydroxy ethyl; scaffold; Spin coating